Effects of Group Activity Play Therapy on Problem Behaviors of Preadolescent Ugandan Orphans - Ojiambo, Deborah; Bratton, Sue C. (Journal of Counseling & Development, 2014)
This randomized controlled study examined the effectiveness of group activity play therapy (GAPT) with 60 displaced Ugandan orphans, ages 10 to 12 years, exhibiting clinical levels of behavior problems. Teachers and housemothers reported that experimental group children demonstrated statistically significant reductions (p < .025) in behavior problems compared with children in the active control condition and that GAPT demonstrated moderate to large treatment effects. Results support GAPT as an effective intervention for troubled Ugandan orphans.
Keywords: Group activity play therapy; Uganda; Outcome research; Behavior problems; Preadolescent orphans